Acanthamoeba castellanii: a new high-throughput method for drug screening in vitro - Ortega-Rivas, Antonio; Padrón, José M.; Valladares, Basilio; Elsheikha, Hany M. (Elsevier, 2016)
Despite significant public health impact, there is no specific antiprotozoal therapy for prevention and treatment of Acanthamoeba castellanii infection. There is a need for new and efficient anti-Acanthamoeba drugs that are less toxic and can reduce treatment duration and frequency of administration. In this context a new, rapid and sensitive assay is required for high-throughput activity testing and screening of new therapeutic compounds. A colorimetric assay based on sulforhodamine B (SRB) staining has been developed for anti-Acanthamoeba drug susceptibility testing and adapted to a 96-well microtiter plate format. Under these conditions chlorhexidine was tested to validate the assay using two clinical strains of A. castellanii (Neff strain, T4 genotype [IC50 4.68±0.6 _M] and T3 genotype [IC50 5.69±0.9 _M]). These results were in good agreement with those obtained by the conventional Alamar Blue assay, OCR cytotoxicity assay and manual cell counting method. Our new assay offers an inexpensive and reliable method, which complements current assays by enhancing high-throughput anti-Acanthamoeba drug screening capabilities.